The trouble with Santa - Sachs, Betsy (New York : Random House, 1990)
When Billy Getten's class puts on a holiday play he learns how different cultures celebrate winter and wonder if there really is a Santa Claus.
Keywords: Holidays - Fiction; Winter - Fiction; Schools - Fiction